Adolescence, food and health - Harding, Ben; Video Educational Australasia (Australia : Video Educational Australasia, 2002)
This program explains the physical needs for nutrients and energy, the emotional needs which foo satisfies, though not always successfully, desire for fast, convenience food in the home and outside, the prevalence and causes of adolescent eating disordrs and some possible solutions initiatives
Title from title screen
Executive producer, Neil Barrett ; graphics, Reece Sanders, Robin Hely ; editor, Conrad Trenton
Presenter: Kate Thwaites
Keywords: Nutrition; Food; Health